Operational modal testing of cantilevered composite plate in subsonic flow - Abang Abdul Majid, Dayang Laila; Che Saffry, Zetty Azleen; Abdullah, Ermira Junita; Mustapha, Faizal; Mohamed Haidzir, Noor Hazira (Public Institution Vibromechanika, 2014)
Conventional modal testing requires a known excitation force in order to extract the modal properties. One particular challenge using this technique is that it can be experimentally complex because of the need for artificial excitation and it also does not represent actual operational condition. The present study had successfully applied a real time modal testing technique for cantilevered flexible composite plate which is exposed to subsonic flow in an open‑looped wind tunnel. The technique only employed two sensors which consist of a single contactless sensing system via a laser vibrometer and an accelerometer as reference. The measured response data was extracted using Frequency Domain Decomposition (FDD) technique. The modal testing was conducted at various air speed and the effects on modal properties are investigated. Conventional modal testing was performed to establish the modal properties. With increasing air speed, the bending modes appeared unaffected, however the frequencies of the torsional modes showed significant increase.